Methodology of determining effective porosity and longitudinal dispersivity of aquifer and the application to field tracer injection test in Southern Hanoi, Vietnam - Thanh, Tong Ngoc; Huy, Trieu Duc; Kenh, Nguyen Van; Tung, Tong Thanh; Quyen, Pham Ba; Hoang*, Nguyen Van (Vietnam Journal of Earth Sciences, 2017)
Groundwater field pumping out and tracer injection test had been carried out at Nghiem Xuyen commune, Thuong Tin district, Hanoi where salinized and fresh groundwater boundary exist in the Pleistocene aquifer. The test was executed with pumping out rate of 9l/sec and tracer injection rate of 0.7l/sec of water with the salt concentration of 5g/l. The interpretation and analysis of the groundwater solute transport parameters by the field pumping out and tracer injection test is a rather complicated and delicate task due to the variability of the temporal boundary conditions. The test results have shown that although the tracer injection time is rather long (up to 60 hours), the tracer breakthrough curve of the tracer concentration of the pumped out water has its very specific characteristic shape, however with some variation due to the test invisible variability of conditions. The results of the parameter identification based on the method of least squares have given effective porosity of 0.32 and longitudinal dispersivity of 2.5m (which give the hydrodynamic dispersion of from D=250m2/day right outside the pumping well screen to D=18m2/day right outside the injection well screen). The minimal sum of squares of the differences between the observed and model normalized tracer concentration is 0.00119, which is corresponding to the average absolute difference between observed and model normalized concentrations of 0.0355 (while 1 is the worse and 0 is the best). The results have also shown that the maximal tracer concentration right outside the pumping out well screen is 6.1 times greater than the tracer concentration of the pumped out water. The distortion flow coefficient αW (the ratio between the flow rate through the injection well section without its presence) and the groundwater flow into the tracer injection well is from 18.66 (at the early testing time) to 10.76 (at the later testing time). References Bear J. and Verruijt A., 1987. Modeling groundwater flow and pollution, D. Reidel Publishing Company, Dordrecht, Holand, 414pp. Brouyère S. 2008. Modeling tracer injection and well-aquifer interactions: a new mathematical and numerical approach. Water Resour. Res, 39(3), 1070-1075. Drost, W., D. Klotz, A. Koch, H. Moser, F. Neumaier, and W. Rauert, 1968. Point dilution methods of investigating ground water flow by means of radioisotopes. Water Resour. Res., 4(1), 125-146. Fetter C.W., 2001. Applied Hydrogeology. Prentice Hall Inc. New Jersey 07458, 598pp. Hall, S.H., 1996. Practical single-well tracer methods for aquifer testing, In: Tenth National Outdoor Action Conference and Exposition, National Groundwater Association, Colombus, Ohio, USA, 11pp. Huyakorn P.S., and Pinder G. F., 1983. Computational Methods in Subsurface Flow. Academic Press, New York, 473pp. Nguyen Van Hoang, 2016. Modeling of pollutant transport in water environment. Vietnam Academy of Science and Technology Publishers, 201pp. Nguyen Van Hoang (project head) (2014-2017). Science and Technology Proposal: Study on the finite element modeling software for simulation of groundwater flow and solute transport by groundwater-application to aquifer in Central plain of Vietnam" codded ĐT.NCCB-ĐHƯD.2012-G/04 supported by NAFOSTED-MOST. Nguyen Van Hoang, Dinh Van Thuan, Nguyen Duc Roi, Le Duc Luong, 2012. Study on the impact of the Tri An reservoir on its downstream groundwater level regime. Vietnam Journal of Earth Sciences, 34(4), 465-476. Nguyen Van Hoang, Pham Lan Hoa, Le Thanh Tung, 2014. Study on the accuracy of the numerical modeling of the groundwater movement due to spatial and temporal discretization. Vietnam Journal of Earth Sciences, 36(4), 424-431. Nguyen Van Hoang and Nguyen Duc Roi, 2015. Finite element method in estimation of lag time of rainfall recharge to Holocene groundwater aquifer in Hung Yen province. Vietnam Journal of Earth Sciences, 37(4), 355-362. Nguyen Van Hoang, Nguyen Thanh Cong, Pham Lan Hoa, Le Thanh Tung, 2016. Study on the characteristics of salinity transport in 2D cross-section unconfined aquifer. Vietnam Journal of Earth Sciences, 38(1), 66-78. Novakowski, K.S., 1992. An evaluation of boundary conditions for one-dimensional solute transport, 1, Mathematical development. Water Resour. Res., 28(9), 2399-2410. Polubarinova-Kotrina P. IA., 1977. Theory of Groundwater. Moscow Science Publishers. 664pp. Tong Thanh Tung, 2015. Specialized report: Interpretation and analysis of aquifer parameters for pumping test at group-well test CHN5 in Nghiem Xuyen-Thuong Tin-Hanoi. Project "Groundwater protection in large cities (city: Hanoi)". Vietnam National Center for Water Resources Planning and Investigation-MoNRE, 16pp. Trieu Duc Huy (Project head), 2015. Science and Technology Proposal: Groundwater protection in large cities (city: Hanoi) approved by MoNRE Minister in Decision 1557/QD-BTNMT dated 30th Aug. 2013. Vietnam National Center for Water Resources Planning and Investigation-MoNRE. Vitaly A. Zlotnik and John David Logan, 1996. Boundary Conditions for Convergent Radial Tracer Tests and Effect of Well Bore Mixing Volume. Papers in the Earth and Atmospheric Sciences, 159pp. Zienkiewicz O. C. and Morgan K., 1983. Finite Elements and Approximation. Academic Press, 328p.